Investigating the biochemical properties of two Nanog orthologues identified in the axolotl - Simpson, Luke A. (2017)
Pluripotent cells give rise to the germ line and the soma. The expression of the Nanog orthologue axNanog is required to establish pluripotency during axolotl development and has a conserved role interacting with axSMAD2 and DPY30 to deposit H3K4me3 through COMPASS. Transcriptome analysis has revealed a second Nanog orthologue: EggNog. EggNog possesses a nearly identical intron- exon structure and yet has a profoundly different role to axNanog, acting to suppress primordial germ cell specification. We aimed to identify whether axNanog and EggNog exhibit different translational regulation or biochemical properties. We also aimed to further define AOE reprogramming of mammalian cells. AOE was probed using western blotting for the presence of axNanog and EggNog proteins. We explored the biochemical properties of axNanog and EggNog using a series of luciferase assays. RT-qPCR and ChIP-qPCR were used to investigate the changes to gene expression and chromatin structure of cells treated with AOE. Luciferase assays demonstrate that axNanog forms stable interactions with axSMAD2 while EggNog shows a reduced affinity to axSMAD2. Western blotting demonstrates that axNanog but not EggNog is present within the axolotl oocyte as a protein. Finally, we show that cells treated with AOE show increased expression of Nanog and Sox2. These data demonstrate that axNanog and EggNog differ in their post-transcriptional regulation and biochemical properties which likely contributes to their differing roles in the developing axolotl.